2020
DOI: 10.1002/cpmc.100
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 Seroconversion in Humans: A Detailed Protocol for a Serological Assay, Antigen Production, and Test Setup

Abstract: In late 2019, cases of atypical pneumonia were detected in China. The etiological agent was quickly identified as a betacoronavirus (named SARS-CoV-2), which has since caused a pandemic. Several methods allowing for the specific detection of viral nucleic acids have been established, but these only allow detection of the virus during a short period of time, generally during acute infection. Serological assays are urgently needed to conduct serosurveys, to understand the antibody responses mounted in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
875
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 729 publications
(921 citation statements)
references
References 13 publications
19
875
1
6
Order By: Relevance
“…15 Antibodies to RBD correlate with neutralizing antibodies 16,17 that could be associated with protection based on studies of other coronaviruses and animal models. [17][18][19][20] The RBD antigen, kindly donated by the Krammer lab (Mount Sinai, New York) 21 , was coupled to magnetic MAGPLEX 6.5 μ m COOH-microspheres from Luminex Corporation (Austin, TX) at a concentration of 40 µg/ml for 10,000 beads/µl, as previously pandemic, at 1/500), were added per plate. Two blank control wells with beads in PBS-BN were set up to measure background signal.…”
Section: Quantification Of Antibodies To Sars-cov-2 By Luminexmentioning
confidence: 99%
“…15 Antibodies to RBD correlate with neutralizing antibodies 16,17 that could be associated with protection based on studies of other coronaviruses and animal models. [17][18][19][20] The RBD antigen, kindly donated by the Krammer lab (Mount Sinai, New York) 21 , was coupled to magnetic MAGPLEX 6.5 μ m COOH-microspheres from Luminex Corporation (Austin, TX) at a concentration of 40 µg/ml for 10,000 beads/µl, as previously pandemic, at 1/500), were added per plate. Two blank control wells with beads in PBS-BN were set up to measure background signal.…”
Section: Quantification Of Antibodies To Sars-cov-2 By Luminexmentioning
confidence: 99%
“…Along these lines, immune patients will have a low risk of pregnancy complications in the event of an embryo transfer, or of propagating the disease when attending a medical facility. Yet, the accuracy of these tests has been debated and it is still unclear how long any immunity lasts and if reinfection is possible [32]. Given the likelihood that this pandemic will continue for many months ahead, we must keep an open mind, and look for what is -and not for fear of what might be.…”
Section: Practical Considerations For Art Treatment Providersmentioning
confidence: 99%
“…. https://doi.org/10.1101/2020 with FcγR signatures to a range of CoV. Amino acid (aa) alignment analyses of NP and S1 proteins 162 showed that there is 91% (NP) and 77% (S1) aa similarity between SARS-CoV-2 and SARS-CoV-1 163 proteins, while SARS-COV-2 and MERS share 47% (NP) aa similarity, hCoVs NL63 and 229E share 164 29% and 26% aa similarity, respectively in NP, and hCoV HKU and 229E share 28% and 27% in S1, 165 respectively (Extended Data Figure 3c Table 3) were screened for SARS-CoV-2 antigen-specific serological profiles (Extended Data 186 Figure 4).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%